The Improvement of Students’ Learning Outcomes Through Demonstration Method in Light and The Properties at Elementary School - Junaidah Junaidah (Universitas Tanjungpura, 2021)
Teachers' skills in using and choosing the right method will greatly help achieve teaching goals. Good teaching must be oriented towards improving the quality of education and the development of students’ learning outcomes. Therefore teachers need to collaborate the teaching methods appropriately. The problem in this research was “How to Improve Students’ Learning Outcomes through Demonstration Methods on Light Material and its properties in fifth grade at SDN 21 Sungai Ambawang?”. The research method used was descriptive research, with classroom action research and collaboration with a teacher. The subjects in this study were 12 students of fifth grade at SDN 21 Sungai Ambawang. Data collection techniques in this study were measurement techniques. While the tool used was the observation sheet. The results showed: (1) The increase in learning outcomes, which was observed from the development of the average daily score on the pre-test was 54.16, while in the post-test cycle I had an increase to 61.94, then in cycle II, there was an increase to 71.94. (2) The effect of the demonstration method on students’ learning outcomes contributed positively, and it was seen that the average percentage of students’ activeness who participated in each cycle had increased, in the cycle, I with average students’ activeness of 67.96 %, and in Cycle II, students’ activeness increased to reach 85.15%. Suggestions (1) Teachers are expected to innovate continuously in the implementation of learning methods to students, especially in demonstration methods with teaching aid, so that learning can run more effectively. (2) It is necessary to increase teachers’ competence in science learning so that the learning process can run smoothly to attract students' interest to take part in learning and improve students’ learning motivation towards science lessons.